The Effect of Curcumin on Biochemical Parameters in 4G-Cell Phone-EMR exposed Male Wistar Rats - Jayanthi.S; Sudha R; Subha V; Manimekalai K; Arulmoli R; Chandra Philip. X (The Bioscan, 2024)
Introduction: Currently, male infertility is the major concern worldwide.Literature is available regarding the negative effects of cell phone radiation on testicular function. The aim of the present study is to document the effect of Curcumin on biochemical parameters in 4G-cell phone-irradiatedmale Wistar rats. Materials and methods: Four-week-old male Wistar rats were split up into four groups, each with six rats. The experiment was done for a period of two months. Control group with no cell phone; CUR-2 group received 100 mg of Curcumin/kg body weight/day; R2 group was exposed to 4G-EMR for two hours per day (5 minutes every half hour from 8 AM to 8 PM); the R+CUR-2 group was exposed to 4G-EMR for two hours per day(5 minutes every half hour from 8 AM to 8 PM) and received 100 mg of Curcumin/kg body weight/day. Serum testosterone, superoxide dismutase (SOD) and malondialdehyde (MDA) in testicular tissue homogenate were measured after the experiment. Results: EMR from4G-cell phonealtered the level of serum testosterone, SOD and MDA in the R2 group as compared with control, CUR-2 and R+CUR-2 groups.Nevertheless, Curcumin effectively shielded those parameters from cell phone-EMR in R+CUR- 2 group. Conclusion: Curcumin can safeguard the testis from the 4G-cell phone radiation inWistar rats.